Interview: The limits and uses of descriptive psychiatry. (August 2013) - Frances, Allen
Allen Frances is the professor emeritus and former chair of the Department of Psychiatry and Behavioral Science at Duke University (NC, USA), and he was the chairperson of the DSM-IV task force. Frances has wide-ranging clinical experience with mood disorders, anxiety disorders, personality disorders and schizophrenia. He is also the author of ' Saving Normal ' and ' Essentials of Psychiatric Diagnosis '.